2021
DOI: 10.3390/su14010219
|View full text |Cite
|
Sign up to set email alerts
|

Towards Effective Environmental Sustainability Reporting in the Large Industrial Sector of Bahrain

Abstract: The industrial sector plays a vital role in economic development; therefore, there is a necessity to integrate sustainability into industrial development to maintain the economy and avoid any degradation impacts on the environment, and thereafter on society. Thus, do Bahraini companies have sustainability reports and if so, are these reports based on GRI guidelines? Has the status of their sustainability reports been analyzed? This research aims to examine the sustainability reports of companies by analyzing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 98 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…In addition, the level of CSR practice in Bahrain-listed companies revealed; 50% below the expected level of sustainability compared to the sustainable international standards (Al-Tarawneh, 2018). One of the most critical results from research on reaching sustainability in the large industrial sector in Bahrain, revealed that SD goals are the key to enhancing the implementation of the corporate report by incorporating all environmental aspects (Rashed, Rashdan, & Ali-Mohamed, 2021). Moreover, A recent study was published investigating the integration between sustainability and CSR in Bahraini Banks' customers.…”
Section: The Research Gapmentioning
confidence: 99%
“…In addition, the level of CSR practice in Bahrain-listed companies revealed; 50% below the expected level of sustainability compared to the sustainable international standards (Al-Tarawneh, 2018). One of the most critical results from research on reaching sustainability in the large industrial sector in Bahrain, revealed that SD goals are the key to enhancing the implementation of the corporate report by incorporating all environmental aspects (Rashed, Rashdan, & Ali-Mohamed, 2021). Moreover, A recent study was published investigating the integration between sustainability and CSR in Bahraini Banks' customers.…”
Section: The Research Gapmentioning
confidence: 99%
“…The 17 UN Sustainable Development Goals (SDGs) and 169 targets are integrated and indivisible, and thus demonstrate the holistic vision of this new universal 2030 Agenda for Sustainable Development and align with the three dimensions of SD [9,65,69,70,75,78,82,83]. According to the UN (2015), the SDGs and targets set will stimulate action by 2030 in areas of critical importance for humanity and the planet, that is, "people," "planet," "prosperity," "peace," and "partnership" [69].…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
“…Fonseca and Carvalho [65] found that the communication of SDGs is more prominent in Portuguese organizations certified in quality, environment, and occupational health and safety (QEOH&S) that disclose their sustainability reports (GRI) on their website. In recent years, the UN SDGs have been approached together with the main MSs (see, e.g., Fonseca and Carvalho [65]), as well as with the ISO standards and other standards (see, e.g., [21,82,83]). Table 1 shows the relationship between the UN SDGs, the primary ISO MSSs, and others.…”
Section: Sustainable Development Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important element is the competitive factors. Most companies want to become "environmental friendly" to create a good social impact on their stakeholders, urging top management to take appropriate environmental disclosures initiatives (Kuo and Chen 2013;Rashed et al 2022). The third important factor recognized by academicians is top manager's characteristics are important facets in determining how businesses respond to institutional pressures and CSR reporting.…”
Section: Introductionmentioning
confidence: 99%